The visual narrative reader - Cohn, Neil (London ; Oxford ; New York ; New Delhi ; Sydney : Bloomsbury Academic, An imprint of Bloomsbury Publishing Plc, 2016)
"Sequential images are as natural at conveying narratives as verbal language, and have appeared throughout human history, from cave paintings and tapestries right through to modern comics. Contemporary research on this visual language of sequential images has been scattered across several fields: linguistics, psychology, anthropology, art education, comics studies, and others. Only recently has this disparate research begun to be incorporated into a coherent understanding. In The Visual Narrative Reader, Neil Cohn collects chapters that cross these disciplinary divides from many of the foremost international researchers who explore fundamental questions about visual narratives. How does the style of images impact their understanding? How are metaphors and complex meanings conveyed by images? How is meaning understood across sequential images? How do children produce and comprehend sequential images? Are visual narratives beneficial for education and literacy? Do visual narrative systems differ across cultures and historical time periods? This book provides a foundation of research for readers to engage in these fundamental questions and explore the most vital thinking about visual narrative. It collects important papers and introduces review chapters summarizing the literature on specific approaches to understanding visual narratives. The result is a comprehensive "reader" that can be used as a resource to researchers, a supplement to courses, and a broad overview of fascinating topics to for anyone interested in the growing field of the visual language of comics and visual narratives"--
"Not all narrative is textual. Images, sequential or non-sequential, have made meaning and told stories since the first cave art and through to the latest 3D movies. This book understands that analyzing this form of narrative is important and fundamental to a complete theory of discourse. Cohn's Visual Narrative Reader explores many forms of image-based narratives. It shows how meaning and sequence is produced and how to approach the discourse analysis involved. Contemporary research on the visual language of sequential images have been scattered across several disciplines: linguistics, psychology, anthropology, art education, and others. Only recently has this disparate research begun to be incorporated into a coherent discipline. This book collects classic and important papers from across disciplinary divides about the comprehension of sequential images, as well as introducing review chapters summarizing the literature from specific approaches to understanding visual narratives. The result is a comprehensive reader that can be used as a resource to researchers, a supplement to courses, and a broad overview of fascinating topics to anyone interested in this growing field studying the visual language of comics and visual narratives"--
Machine generated contents note: 1.Interdisciplinary Approaches to Visual Narrative / Neil Cohn -- 1.Introduction -- 2.Visual language theory -- 3.Studying visual narratives -- 4.Onwards and upwards -- References -- pt. I Theoretical Approaches to Sequential Images -- 2.Linguistically Oriented Comics Research in Germany / John Bateman -- 1.Introduction -- 2.Orienting concepts -- 3.A broadly chronological review -- 4.A brief critical evaluation of the story so far -- 5.Conclusions and future directions -- Acknowledgements -- Notes -- References -- 3.No Content without Form: Graphic Style as the Primary Entrance to a Story / Pascal Lefevre -- 1.Introduction -- 2.The nature of drawings -- 3.Biological foundations of the efficiency of line drawing for human visual perception -- 4.From strokes to style -- 5.A model to study graphic style -- 6.Conclusion -- Notes -- References -- 4.Conceptual Metaphor Theory, Blending Theory, and Other Cognitivist Perspectives on Comics / Charles Forceville -- 1.Introduction -- 2.Conceptual metaphor theory, blending theory, image schemas and the embodied mind -- 3.Studies on cartoons drawing on CL, CMT and BT -- 4.Studies on comics drawing on CL, CMT and BT -- 5.Other pertinent cognitivist approaches -- 6.Concluding remarks and further research -- Acknowledgement -- Note -- References -- 5.Relatedness: Aspects of Textual Connectivity in Comics / Mario Saraceni -- 1.Aims of the chapter -- 2.Theoretical background -- 3.Towards a linguistic-visual and textual-cognitive model of relatedness -- 4.Conclusion -- Notes -- References -- 6.A Little Cohesion between Friends; Or, We're Just Exploring Our Textuality: Reconciling Cohesion in Written Language and Visual Language / Eric Stainbrook -- 1.Introduction -- 2.Cohesion in written language -- 3.Cohesion in visual language art -- 4.Cohesion in visual language revisited -- 5.Cohesion through writing in visual language: framed and graphic text -- 6.Cohesion through writing in visual language: dialogue balloons -- 7.Cohesion through writing in visual language: captions -- 8.Discussion -- References -- pt. II Psychology and Development of Visual Narrative -- 7.Manga Literacy and Manga Comprehension in Japanese Children / Jun Nakazawa -- 1.Introduction -- 2.Literacy for manga drawing and reading -- 3.Relation between manga reading literacy and story comprehension -- 4.Eye-tracking behaviour with manga reading -- 5.A cognitive processing model of manga reading comprehension -- 6.Applications of manga -- 7.Conclusion -- Acknowledgement -- References -- 8.What Happened and What Happened Next: Kids' Visual Narratives across Cultures / Brent Wilson -- 1.Child art versus visual narrative -- 2.Why do kids make visual narratives? -- 3.Case studies of visual narrative and artistic giftedness -- 4.Elicited sequential narratives: within and across cultural studies -- 5.Cross-cultural studies, visual narrative themes and compositional modes in Australia, Egypt, Finland and the United States -- 6.Story-drawing themes, compositions, and styles in a Giza village and Cairo moderate-income and wealthy neighbourhoods -- 7.Visual narrative worlds without end: tales from Japan -- 8.Manga characters and how to be Japanese -- 9.A nation of visual narrators: distributed pedagogy -- 10.The end -- for now -- Notes -- References -- pt. III Visual Narratives across Cultures -- 9.The Walbiri Sand Story / Nancy Munn -- 1.The sand story -- 2.Vocabulary -- 3.The flow of graphic scenes in storytelling -- 4.Types of scenes -- 5.Scene cycling and narrative content -- 6.Figure types and story contexts -- 7.Discussion -- Notes -- References -- 10.Alternative Representations of Space: Arrernte Narratives in Sand / David P. Wilkins -- 1.Introduction -- 2.The spatial properties of sand drawing -- 3.The child's acquisition of sand-drawing conventions -- 4.Narrative behaviour with accompanying drawings -- 5.Conclusion -- Acknowledgements -- Notes -- References -- 11.Sequential Text-Image Pairing among the Classic Maya / Jesper Nielsen -- 1.Introduction -- 2.The cultural context and media of Maya text-image pairings -- 3.Sequential text-image pairing as a new subcategory of conjoined text and image -- 4.The organization of images -- 5.Narrative sequentiality in Maya imagery -- 6.Determining the directional decoding of sequential text-image pairing -- 7.The techniques and idioms of Maya sequential art -- 8.A sample analysis: the `Regal Bunny Pot' (K1398) -- 9.Conclusions -- Acknowledgements -- Notes -- References -- 12.Linguistic Relativity and Conceptual Permeability in Visual Narratives: New Distinctions in the Relationship between Language(s) and Thought / Neil Cohn -- 1.Introduction -- 2.Permeability and relativity in basic lexical items -- 3.Conceptual metaphor -- 4.Paths and motion events -- 5.Windowing of attention -- 6.Spatial orientation -- 7.Conclusion -- Acknowledgements -- Notes -- References.
Includes bibliographical references and index.
EHN
Trim Education
Keywords: Semiotics -- Psychological aspects; Visual literacy; Visual education; Readers; Sequence (Linguistics); Cognition; Psycholinguistics; English language